Synthesis and Characterization of an Adsorbent from Chicken Eggshell and Its Application for Methyl Orange - Eka Sri Yusmartini; Mardwita Mardwita; Eko Ariyanto; Wahyu Triaji Rahadianto; Ikbal Oktaviansyah; Muhammad Dzaky Muzhaffar (UNIVERSITAS SEBELAS MARET (UNS), 2026)
Eggshell is a part that protects egg components from various external threats, including chemical, physical, and biological factors. This study aimed to obtain an adsorbent from chicken eggshells using physical and chemical activation techniques. The quality of the eggshell-derived adsorbent was assessed and compared with the Indonesian National Standard (SNI) 1995, with a focus on parameters such as ash content, moisture content, and iodine absorption. The adsorbent obtained was applied to a solution of methyl orange, and Fourier transform infrared spectroscopy (FTIR) analysis was conducted before and after the adsorption process. Furthermore, the study stages include adsorbent preparation, activation, and adsorption. The adsorbent weight for this process was 17 grams, with time intervals of 15, 30, 45, 60, and 75 minutes. The results showed that both physically activated as well as physical and chemical activated adsorbents met the SNI 1995 standard, based on the parameters of water content (1.73% and 2.86%), ash content (8.18% and 6.745), and iodine absorption (761.40 mg/g and 774.09 mg/g). FTIR analysis confirmed the presence of a hydrocarbon and an OH group in the structure before and after adsorption. The optimum methyl orange adsorption capacity was achieved at an adsorbent mass of 17 grams and a contact time of 60 minutes, resulting in removal efficiencies of 20.38% for physical activation and 24.11% for physical and chemical activation.